Domination and the arts of resistance: Hidden transcripts - Scott, James C. (London Yale University Press, 1990)
Confrontations between the powerless and the powerful are laden with deception--the powerless feign deference and the powerful subtly assert their mastery. Peasants, serfs, untouchables, slaves, labourers, and prisoners are not free to speak their minds in the presence of power. These subordinate groups instead create a secret discourse that represents a critique of power spoken behind the backs of the dominant.